A WORLD SHARIA BANKING CAPITAL STRUCTURE: VALUE, SIZE, PROFITABILITY AND DIVIDEND POLICY - Wardana, Guntur Kusuma; Barlian, Noer Aisyah; Ichsan, Chairil Fadillah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Ensuring financial stability and continuity of Islamic banking activities relies significantly on maintaining an appropriate capital structure. This study, examines the factors impact the financial framework of Islamic banking on a global scale, utilises data from 19 Islamic banks located in eleven distinct countries. Panel data regression using a chance effect model employe to conduct data analysis. The research findings indicate, the capital structure of Islamic banking worldwide is positively influenced by bank value and profitability. However, the size of the bank and its dividend policy do not exert a substantial impact. These findings suggest that Islamic bank management should prioritise improving bank value and profitability in order to achieve an optimal capital structure. Additionally, these findings provide fresh insights into the factors that influence capital structure in the worldwide Islamic banking industry. This study makes a valuable contribution to the formulation of policies and implementation of effective strategies for managing the capital structure of sharia banking. Additionally, it aims to promote the growth and stability of the sharia financial industry as a whole